Dari Societeit Concordia Menuju Gedung Merdeka: Memori Kolektif Kemerdekaan Asia-Afrika - Achmad Sofyan (Diponegoro University, 2019)
As a part of the cities in the colonization age, Bandung had a lot of colonial building. The buildings were Gemeente Huis, Gedung Sate, Bandung Technology Institute, Pasteur Institute, Societeit Concordia, and many others building. It cannot be rejected that the colonial architecture always has a concept and meaning related to the structure when it builds. So that, the building had never extinct by the ages. Even though the function of buildings changed as public space, but it still had some memories and histories to remember. Based on that explanation, this paper has a purpose of describing the concept of cities of mind that introduced by Pierre Nora attached on a colonial building Societeit Concordia that led on the name changes as Gedung Merdeka because of political purpose in a declaration of independence by the nation of Asia-Afrika at Bandung. This article is used as the historical method. It analyzes the meaning changes that happened on collective memory after the changes on the name of Gedung Merdeka building